INTEGRASI TEKNOLOGI PENDIDIKAN BERBASIS ARCS: MENINGKATKAN MOTIVASI BELAJAR GENERASI ALPHA DI RUMAH BELAJAR SOLA FIDEI JAKARTA UTARA - Simatupang, Jhonnedy; Lumban Tungkup, Hizkia (Sekolah Tinggi Teologi Bethel The Way Jakarta, 2025)
The advancements in technology and education have significantly influenced the learning patterns of Generation Alpha, In the learning process, students tend to use technology for things outside of learning activities. This study aims to analyze the application of educational technology based on the ARCS model (Attention, Relevance, Confidence, and Satisfaction) in enhancing the learning motivation of this generation. Employing a descriptive qualitative method through interviews with five students from Rumah Belajar Sola Fidei in North Jakarta aged 12 to 14, along with literature studies supported by NVivo software, the research reveals that technology integrating ARCS elements can boost engagement and learning motivation among Generation Alpha. Tools that capture attention, are relevant, build self-confidence, and provide satisfaction have proven effective in creating enjoyable and meaningful learning experiences. Consequently, this study seeks to examine how technology can strengthen each element of ARCS to create a more engaging, relevant, and motivating learning environment within the context of digital education. In conclusion, the ARCS model can serve as an effective strategy for enhancing learning motivation among Generation Alpha in the digital age.